Entrepreneurial Productivity of Single and Non Single Women of Kathmandu Metropolitan City - Nepal, Ratna Mani; Ramtel, Om Kumari (Management Dynamics, 2020)
Despite that women’s socio-economic status is poor, there involvement in entrepreneurial development is low. Data shows that women’s participation in income generating activities and their access to property is quite unsatisfactory. Globally, only eight percent small scale-manufacturing units are owned and operated by women. Compared to the universal statistics, Nepal’s scenario is different because the country owns more than six lakhs small scale manufacturing units. In these units women’s participation is relatively higher. Certain ethnic community, especially the Newar and Tibeto–Burman highland groups such as the Sherpa, Gurung and Thakali, are known to have a long tradition of women being involved in small business enterprises. However, women’s ownership of these enterprises is extremely low. This study aims to examine the entrepreneurial status of single and non-single women who are engaged in entrepreneurial activities in Kathmandu Metropolitan city. It also analyzes the entrepreneurial productivity of the enterprises run by the women. In order to discuss the objectives, primary data was collected from field work. This study found that single women’s involvement in the small businesses was encouraging. The entrepreneurial productivity of the enterprises run by single-women was higher than non-single women.